Treatment Of The Gelatin Wastewater With Ozone Peroxide Advanced Oxidation Process - Sekaringgalih, Ratri; Alif Nur Laili Rachmah; Gessantara, M. Febbia (Menara: Jurnal Teknik Sipil, 2023)
This research aims to decrease the level of COD, BOD5, and color in the liquid waste of the gelatin industry by using the ozonation process and hydrogen peroxide in order to meet the quality standards of the seaweed industrial waste. The reaction between ozone and peroxide called the peroxone process is one of the Advanced Oxidation Processes (AOPs). The combination of ozone with peroxide can result in a cheaper process. The result shows the lowest COD at the time of ozonation 160 minutes with the addition of hydrogen peroxide 30 ml was 932.39 mg/L (37.03%), the lowest BOD5 at ozonation 160 minutes with the addition of 25 ml hydrogen peroxide was 164.32 mg/L (48%) and the lowest color at 80 minutes of ozonation with the addition of 10 ml of hydrogen peroxide is 158 (73.75%). In the AOPs, the decrease in COD and BOD5 was higher than that of ozonation without hydrogen peroxide..